Crosstalk between lysine methylation and phosphorylation of ATG16L1 dictates the apoptosis of hypoxia/reoxygenation-induced cardiomyocytes. Issue 5 (4th May 2018) - Song, Huiwen; Feng, Xing; Zhang, Min; Jin, Xian; Xu, Xiangdong; Wang, Lin; Ding, Xue; Luo, Yunmei; Lin, Fengqin; Wu, Qin; Liang, Guiyou; Yu, Tian; et al.
ABSTRACT: Post-translational modifications of autophagy-related ( ATG ) genes are necessary to modulate their functions. However, ATG protein methylation and its physiological role have not yet been elucidated. The methylation of non-histone proteins by SETD7, a SET domain-containing lysine methyltransferase, is a novel regulatory mechanism to control cell protein function in response to various cellular stresses. Here we present evidence that the precise activity of ATG16L1 protein in hypoxia/reoxygenation (H/R)-treated cardiomyocytes is regulated by a balanced methylation and phosphorylation switch. We first show that H/R promotes autophagy and decreases SETD7 expression, whereas autophagy inhibition by 3-MA increases SETD7 level in cardiomyocytes, implying a tight correlation between autophagy and SETD7. Then we demonstrate that SETD7 methylates ATG16L1 at lysine 151 while KDM1A/LSD1 (lysine demethylase 1A) removes this methyl mark. Furthermore, we validate that this methylation at lysine 151 impairs the binding of ATG16L1 to the ATG12–ATG5 conjugate, leading to inhibition of autophagy and increased apoptosis in H/R-treated cardiomyocytes. However, the cardiomyocytes with shRNA-knocked down SETD7 or inhibition of SETD7 activity by a small molecule chemical, display increased autophagy and decreased apoptosis following H/R treatment. Additionally, methylation at lysine 151 inhibits phosphorylation of ATG16L1 at S139 by CSNK2 which was previously shown to be critical for autophagy maintenance, and vice versa . Together, our findings define a novel modification of ATG16L1 and highlight the importance of an ATG16L1 phosphorylation-methylation switch in determining the fate of H/R-treated cardiomyocytes.